Chest compression components (rate, depth, chest wall recoil and leaning): A scoping review. (1st January 2020) - Considine, Julie; Gazmuri, Raúl J.; Perkins, Gavin D.; Kudenchuk, Peter J.; Olasveengen, Theresa M.; Vaillancourt, Christian; Nishiyama, Chika; Hatanaka, Tetsuo; Mancini, Mary E.; Chung, Sung Phil; Escalante-Kanashiro, Raffo; Morley, Peter
Abstract: Aim: To understand whether the science to date has focused on single or multiple chest compression components and identify the evidence related to chest compression components to determine the need for a full systematic review. Methods: This review was undertaken by members of the International Liaison Committee on Resuscitation and guided by a specific methodological framework and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for scoping reviews (PRISMA-ScR). Studies were eligible for inclusion if they were peer-reviewed human studies that examined the effect of different chest compression depths or rates, or chest wall or leaning, on physiological or clinical outcomes. The databases searched were MEDLINE complete, Embase, and Cochrane. Results: Twenty-two clinical studies were included in this review: five observational studies involving 879 patients examined both chest compression rate and depth; eight studies involving 14, 285 patients examined chest compression rate only; seven studies involving 12001 patients examined chest compression depth only, and two studies involving 1848 patients examined chest wall recoil. No studies were identified that examined chest wall leaning. Three studies reported an inverse relationship between chest compression rate and depth. Conclusion: This scoping review did not identify sufficient new evidence that would justify conducting new systematic reviews or reconsideration of current resuscitation guidelines. This scoping review does highlight significant gaps in the research evidence related to chest compression components, namely a lack of high-level evidence, paucity of studies of in-hospital cardiac arrest, and failure to account for the possibility of interactions between chest compression components.